ChemInform Abstract: Heck—Matsuda Reaction of Arenediazonium Salts in Water. Issue 32 (18th July 2013) - Salabert, Jordi; Sebastian, Rosa Maria; Vallribera, Adelina; Civicos, Jose Francisco; Najera, Carmen
Abstract The presented protocol is general and environmentally friendly, does not require any base or additives and proceeds with low catalyst loading.